2013
DOI: 10.1002/etc.2214
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of the antimicrobial ciprofloxacin with soil, peat, and aquatic humic substances

Abstract: Natural organic matter (NOM) is implicated in the binding of antibiotics by particles in soils and waters. The authors' previous computational study revealed structural rearrangement of both hydrophilic and hydrophobic moieties of NOM to favor H-bonding and other intermolecular interactions, as well as both competition with ion-exchange reactions and bridging interactions by NOM-bound divalent cations. The importance of these interactions was investigated using fluorescence-quenching spectroscopy to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 62 publications
2
39
2
1
Order By: Relevance
“…If adsorption is the principal mechanism for sequestration of ciprofloxacin in organic wastes, this mechanism is likely to be enhanced by the compost process because composting reduces particle sizes and therefore increases total adsorptive surface area (7). Presumably, the same adsorptive mechanisms would also neutralize other antibiotics and pharmaceuticals that can be sequestered via adsorptive forces (13,29). While it is probable that other mechanisms such as biological degradation and high temperature contribute to the degradation of ciprofloxacin in the compost, the methods used in this study did not allow separation of these effects.…”
Section: Discussionmentioning
confidence: 93%
“…If adsorption is the principal mechanism for sequestration of ciprofloxacin in organic wastes, this mechanism is likely to be enhanced by the compost process because composting reduces particle sizes and therefore increases total adsorptive surface area (7). Presumably, the same adsorptive mechanisms would also neutralize other antibiotics and pharmaceuticals that can be sequestered via adsorptive forces (13,29). While it is probable that other mechanisms such as biological degradation and high temperature contribute to the degradation of ciprofloxacin in the compost, the methods used in this study did not allow separation of these effects.…”
Section: Discussionmentioning
confidence: 93%
“…The composition of humic substances depends on the initial biomaterial content and on the groups of microorganisms, under the action of which the transformation occurs (Aristilde and Sposito 2013). Industrially produced humic materials demonstrated no or insignificant impact on the surface tension of their solutions, whereas the humic acids isolated from peat demonstrated significant impacts on the surface tension of their solutions, i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Humic substances (HS), as the major fraction of DOM in natural water, are expected to play primary roles in binding with antibiotics of both hydrophilic and hydrophobic moieties owing to H-bonding and other intermolecular interactions 17 . It has been shown that ciprofloxacin can bind with HS due to intermolecular interactions, and both the pH and the types of HS determine the ciprofloxacin-HS complexes 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ciprofloxacin can bind with HS due to intermolecular interactions, and both the pH and the types of HS determine the ciprofloxacin-HS complexes 17 . Of note, under environmentally relevant pH conditions, the primary driver for ciprofloxacin adsorption onto soil organic matter is a cation-exchange reaction involving a mediating electrostatic attraction between the positively charged group of the antibiotic and the negatively charged HS group 17, 21 . In fact, the binding of ciprofloxacin with HS mainly depends on the van der Waals interaction, H-bonding and electrostatic interactions 17 .…”
Section: Introductionmentioning
confidence: 99%